Computational Search for Possible Mechanisms of 4‐Thiazolidinones Anticancer Activity: The Power of Visualization. Issue 3 (11th March 2014) - Devinyak, Oleg; Havrylyuk, Dmytro; Zimenkovsky, Borys; Lesyk, Roman
Abstract Public databases of NCI‐60 tumor cell line screen results and measurements of molecular targets in the NCI‐60 panel give the opportunity to assign possible anticancer mechanism to compounds with positive outcome from antitumor assay. Here, the novel protocol of NCI databases mining where inferences are based on the visualization is presented and utilized with the aim to identify putative biological routes of 4‐thiazolidinones anticancer effect. As a result, highly potent 4‐thiazolidinone‐pyrazoline‐isatin conjugates show the similarity of activity patterns with puromycin and CBU‐028 and their pattern is also highly correlated with fraction of methylated CpG sites in CD34, AF5q31 and SYK. Several compounds from this group show strong negative correlation with fraction of methylated CpG sites in HOXA5. Thiopyrano[2, 3‐d][1, 3]thiazol‐2‐ones bearing naphtoquinone fragment were found to possess the same activity pattern as fusarubin does. But none of the studied 4‐thiazolidinone derivatives has activity fingerprint similar to standard anticancer agents. The obtained results bring medicinal chemistry closer to the understanding of basic nature of 4‐thiazolidinones effect on cancer cells.